Medical observations and injury analysis: All Girls Touch Rugby Championship 2024 - Nazarudin, Mohamad Nizam; Tan, Yong Qin; Okilanda, Ardo; Ockta, Yovhandra; Nugraha, Reshandi (CV Rezki Media, 2025)
Background: Touch rugby is a high-intensity, non-contact sport requiring agility, speed, and coordination. This study analyzes injury distribution, treatment effectiveness, and preventive measures among youth touch rugby players. Objectives: This study examined injury patterns among adolescent female athletes during the 2024 All-Girls Touch Rugby Championship (AGTR 2024). Methods: A retrospective observational study was conducted using medical reports from the two-day All-Girls Touch Rugby Championship 2024 (AGTR 2024) at Universiti Putra Malaysia. The study examined 484 female athletes (ages 9–18 years), with 176 injuries recorded and categorized as soft tissue injuries (52.3%), abrasions (23.9%), and sprains (14.2%). Descriptive statistics were used to assess injury distribution, while chi-square analysis (χ² = 10.45, p < 0.01) evaluated the relationship between injury type and age group. Results: Younger players (10–14 years) sustained more abrasions (60%), whereas older athletes (15–18 years) had a higher incidence of soft tissue injuries (68%). Injuries increased by 66.7% on Day 2, highlighting the impact of cumulative fatigue and tournament intensity. Ice therapy (68%) and bandaging (55%) were the most utilized treatments, with only 7% of cases requiring outpatient referrals. Conclusions: Findings underscore the need for structured warm-ups, enhanced hydration protocols, and targeted strength training to reduce injury risks. The study emphasizes the role of injury surveillance, playing surface improvements, and gender-specific training programs in preventing injuries and enhancing athlete safety. Implementing evidence-based preventive strategies can promote the long-term development and sustainability of touch rugby for adolescent athletes. Future research should focus on longitudinal injury tracking and tailored intervention strategies.